Reception of Qur'anic Verses in the Practice of Penglaris in the Local Economy Context: A Study in Sungai Penuh City: Resepsi Ayat-Ayat Al-Qur'an dalam Praktik Penglaris dalam Konteks Ekonomi Lokal: Sebuah Studi di Kota Sungai Penuh - Pratama, M. Raditya Ridho; Fadil, Marjan (Institut Agama Islam Negeri Kerinci, 2024)
This study critically investigates the practice of using Qur’anic verses as “penglaris” (sales enhancers) within the local economic context of Sungai Penuh City, Jambi. Adopting the Living Qur’an framework and reception theory, and integrating phenomenological, mystical, and cultural contestation approaches, the research reveals how the meanings and functions of “penglaris” verses are constructed, negotiated, and enacted by traders, traditional leaders, and religious authorities. Qualitative data were collected through in-depth interviews with 20 key informants and participant observation in three traditional markets. Major findings indicate that: First, verses such as Al‑Fātiḥah, Ayat al-Kursī, and the “Thousand Dinar” prayer are pragmatically employed as spiritual instruments to boost traders’ confidence and optimism; Second, belief in the barakah (blessing) of these verses underscores a mystical dimension inherent in the text, even as users affirm that sustenance ultimately remains Allah’s prerogative; Third, the practice functions as a competitive tool in market rivalry while also becoming a hegemonic norm within the community; and Fourth, a contestation of meaning arises between traditional authorities, who accept the practice as cultural heritage, and religious authorities, who critique it as potentially shirk (associationism). This study contributes to the development of Qur’anic reception methodology in contemporary tafsīr studies and broadens understanding of the interaction between sacred text, local traditions, and economic dynamics.